Traditional Communication and Language Power In The Deliberative Culture Of “Lonto Leok” - Manafe, Yermia Djefri; Hadi, Ido Prijana; Jama, Karolus Budiman (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Communication of traditional elite power relations and language power over silent groups in the